2012
DOI: 10.1007/s00381-011-1660-1
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental functioning of infants with untreated single-suture craniosynostosis during early infancy

Abstract: Untreated SSC is associated with an increased incidence of developmental delay during early infancy, with motor skills appearing the most vulnerable to impairment during this developmental phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
44
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 45 publications
6
44
0
5
Order By: Relevance
“…This rate is consistent with findings of several studies that examined developmental attainment, learning disability, and speech and language abnormalities in isolated SC. 7,8,13,14,33,44,46 Although, in 1982, Renier et al 41 found that raised ICP was correlated with lower IQ, more recent studies 6,23,34 have failed to confirm the relationship between elevated ICP and neurocognitive outcomes in SC or other single-suture craniosynostosis. The lack of a correlation between developmental delay and raised ICP found in the present study supports the hypothesis that there is no simple causal relationship between ICP and neurocognitive anomalies found in SC.…”
mentioning
confidence: 99%
“…This rate is consistent with findings of several studies that examined developmental attainment, learning disability, and speech and language abnormalities in isolated SC. 7,8,13,14,33,44,46 Although, in 1982, Renier et al 41 found that raised ICP was correlated with lower IQ, more recent studies 6,23,34 have failed to confirm the relationship between elevated ICP and neurocognitive outcomes in SC or other single-suture craniosynostosis. The lack of a correlation between developmental delay and raised ICP found in the present study supports the hypothesis that there is no simple causal relationship between ICP and neurocognitive anomalies found in SC.…”
mentioning
confidence: 99%
“…Es relevante mencionar que la mayoría de los estudios que mencionan deficiencias en niños con craneosinostosis carecen de grupo control (e.g [25][26][27][28][29] ), sólo son referidos a normas, por lo que sería importante conocer si los déficits encontrados persisten cuando se compara el desempeño con un grupo control pareado.…”
Section: Del Nacimiento a Los 3 Años De Edadunclassified
“…Por su parte, Da Costa et al 26 mencionan que los índices mental y motor de niños con craneosinostosis son más bajos que lo esperado por el grupo normativo, aunque las puntuaciones aún caen dentro de los rangos normales; en sentido opuesto, Kapp-Simons et al 28 encontraron que el 16% y el 38% de su muestra obtuvo puntuaciones por debajo de una desviación estándar en el índice mental y psicomotor. Speltz et al 31 en una comparación con un grupo control encontraron diferencias estadísticamente significativas en los índices que evalúan las Escalas Bayley.…”
Section: Del Nacimiento a Los 3 Años De Edadunclassified
See 1 more Smart Citation
“…Similar findings have been reported in a well-designed study of Australian infants who were followed with similar developmental measures. 14 A key question is whether these delays persist into the school-age years and manifest as learning disabilities or other problems in need of intervention. 15 Few neurodevelopmental studies have focused on children with SSC beyond age 3, [16][17][18][19][20] and most of these studies have lacked control groups 17,19,20 or used methods other than testing to estimate developmental progress.…”
mentioning
confidence: 99%